Construction of ion transport channels by grafting flexible alkyl imidazolium chain into functional poly(arylene ether ketone sulfone) as anion exchange membranes. (12th October 2017) - Xu, Jingmei; Liu, Bingxin; Luo, Xueyan; Li, Minghui; Zang, Huan; Zhang, Huixuan; Wang, Zhe
Abstract: A new series of imidazolium-functionalized anion exchange membranes (AEMs), based on poly (arylene ether ketone sulfone) containing pendant amino groups (Am-PAEKS) have been prepared. The structure of the copolymers is characterized by FT-IR and 1 H NMR spectra. The properties of the imidazolium-functionalized Am-PAEKS (Im-Am-PAEKS) including ionic conductivity, dimensional stability, thermal stability, fuel cell performance and mechanical property are investigated thoroughly. The hydroxide conductivities of the prepared membranes are in the range of 1.1 × 10 −2 –13.9 × 10 −2 S cm −1 (20–80 °C). The membranes exhibit excellent alkaline stability including high thermal stability and mechanical property after soaking in 2 M NaOH aqueous solution for 300 h. This study indicates that the imidazolium-functionalized membranes containing pedant amino groups have the potential to be applied in alkaline fuel cells. Graphical abstract: Highlights: Imidazolium-functionalized AEMs containing pendant amino group were prepared. The introduced amino groups can promote the formation of hydrogen-bond network. Hydrogen-bond network is beneficial for the construction of ion transport channels. The prepared AEMs exhibited desirable dimensional stability and alkaline stability.